Using formative assessment to differentiate mathematics instruction, grades 4-10 : seven steps to maximize learning - Laud, Leslie (Corwin, 2011)
Seven easy steps to differentiating math instruction for busy teachers Staff development expert Leslie Laud provides a clear roadmap for using formative assessment to differentiate mathematics instruction for students in Grades 4-10. She presents a comprehensive framework of seven research-based practices that show teachers how to: Get started and establish norms Implement formative assessment Create tiered lessons Manage a multitasking classroom effectively Tested, reviewed, and enhanced by experienced math teachers, the book includes practical examples, reproducibles.